Recurrent formulas and moves in writing research article conclusions among native and nonnative writers - Hadi Kashiha, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
For years, writing academic research articles (RAs) has gained abundant attention from scholars. This is obviously motivated by the fact that writing RAs is an important endeavor through which writers are able to communicate with members in their discourse community with an owned academic voice to perpetuate an identity. This voice is facilitated through the frequent and efficient use of formulaic sequences such as lexical bundles. This study aims to investigate the use of lexical bundles in two different corpora of 200 RA conclusions written by native and Iranian non-native writers. The comparison is premised on the notion that there may be linguistic differences between the two groups of writers and the comparison could serve to highlight how communicative purposes could be conveyed by the bundles in the moves and steps of the conclusions differently. Findings demonstrated that native writers relied more on the use of lexical bundles in writing conclusions. Structurally, the majority of the bundles found in the two corpora were noun or prepositional phrases. While native authors were more inclined to the use of dependent clauses, the bundles found in the L2 corpus contained more verb phrases. Further analysis of the bundles in the moves and steps of the conclusions revealed some marked variations between the two groups. Most of these expressions in the L2 corpus were used in more than one move or step, while in the native corpus, a group of lexical bundles were found to belong to only one move or step of a move.